Expectations of student with disability living in off-campus student housing in Ghana: a Gap Model approach - Elvis Attakora-Amaniampong; Miller Williams Appau; Issaka Kanton Osumanu (PSU Research Review)
Purpose – Previous students' housing studies have neglected the need to study all-inclusive student housing and quality of services delivery among students with disability. This study explores the expectations in students' housing among university students living with disabilities (SWDs) in Ghana. Design/methodology/approach – The study adopted a mixed-methods approach, involving 423 SWD selected from five public and three private universities across Ghana. Grounded on the Gap Model, the study employed exploratory factor analysis to extract factors of service quality delivery and universal building design for SWD living in off-campus students' housing. Findings – The study uncovered that, expectations of SWD regarding building design specifications hinges more on inbuilt universal design than external building environment designs. SWD are more interested in safety, health, managerial assurances and security. In all, five factors provided a huge gap in services quality delivered by off-campus students' housing. Practical implications – The Gap Model technique offers a framework that provides an insight for students' housing investors, managers, researchers and local authorities that provides an insight on the needs of SWD in student housing, thus making it possible to attain satisfactions amongst SWD. Originality/value – Unlike health-related studies that deals with expectations of all-inclusive buildings for persons with disability in hospitals, this study uniquely uncovered the expectations of services delivery and building design support to SWD in the Ghanaian context.